The Homonational Archive: Sexual Orientation and Gendered Identity Refugee Documentation in Canada and the USA. Issue 3 (27th May 2017) - Murray, David A. B.
ABSTRACT: Anthropologists and social scientists are regularly asked to submit 'expert' reports focusing on social, cultural or political conditions in refugee-producing nation states on behalf of human rights organisations or lawyers representing refugee claimants in the Global North. In this paper I reflect on my own participation in the production of these reports and the cumulative effect of expert documents on sexual orientation and gender identity refugee claims as they accrue in the paper and electronic folders of courts, and state immigration and refugee departments, producing a governmental archive of knowledge on sexual orientation and gendered identity. I argue that these archives reinforce homonationalist discourses which contain a highly delimited – neo-liberal, classed and raced – definition of sexual and gendered identity that is folded into some nation states' discourses of the good immigrant and proper citizen, simultaneously creating its opposite, the bad immigrant and deviant citizen.